Study on photocatalytic mineralization of various azo dyes under solar light irradiation - Wan Fadhilah Wan Mohd Khalik (School of Environmental Engineering, University Malaysia Perlis, 2014)
The main purpose of this research was to evaluate the mineralization of various azo dyes by solar photocatalytic process. The main photocatalyst and azo dye used in this study was zinc oxide (ZnO) and New Coccine (NC), respectively. In the first section, the study was to compare the solar photocatalytic between decolorization of Orange G and New Coccine. The comparison between the azo dyes was determined through several operating parameters such as with and without solar light irradiation, initial dye concentration, catalyst dosage, pH and with and without aeration.